The relationship between teachers' perceptions of organizational justice and job satisfaction - Alanoglu, Muslim; Demirtas, Zulfu (Pegem Akad Yayincilik Egitim Danismanlik Hizmetleri Tic Ltd Sti, 2019)
The purpose of this research is to determine the relationship between teachers' perceived organizational justice and job satisfaction. This quantitative study is designed in relational survey model. The sample of the research consists of 396 teachers working in the public high schools located in four central provinces of Mersin city. Organizational Justice Scale and Job Satisfaction Scale were used as data collection tools in the study. Arithmetic mean, standard deviation, t test, ANOVA and correlation analysis were performed by using SPSS 21 package program. According to the findings, the level of perception of teachers' organizational justice and job satisfaction is high. Of the demographic variables, only professional tenure caused meaningful differentiation at job satisfaction. Other variables did not cause meaningful differences at organizational justice and job satisfaction perceptions. There is a meaningful, low level and positive relationship between organizational justice and job satisfaction perception levels.
Öğretmenlerin örgütsel adalet ve iş doyumu algilari arasindaki ilişki
Keywords: Teacher; Organizational justice; Job satisfaction